Evidence of Mixed‐Ligand Complexes in Cu−CHA by Reaction of Cu Nitrates with NO/NH3 at Low Temperature. Issue 16 (11th June 2019) - Negri, Chiara; Borfecchia, Elisa; Cutini, Michele; Lomachenko, Kirill A.; Janssens, Ton V. W.; Berlier, Gloria; Bordiga, Silvia
Abstract: The reactivity with a NO/NH3 mixture of Cu‐nitrate complexes formed on the surface of a Cu−CHA catalyst active in the Selective Catalytic Reduction of NOx with NH3 (NH3 −SCR) was followed at 50 °C by in situ spectroscopic techniques. The catalyst (Si/Al=15; Cu/Al=0.5) was first exposed to NO/O2 (mimicking the SCR oxidative half‐cycle), mainly resulting in the formation of chelating bidentate framework‐interacting Cu II ‐nitrates. These intermediates were gradually detached from the framework in the presence of NO/NH3 (or NH3 alone), forming mixed‐ligand mobile [Cu II (NH3 )3 (NO3 )] + complexes, with infrared bands at 1624 (δNH3 ), 1430 and 1325 cm −1 (monodentate nitrate νNO2asym and νNO2sym, respectively). X‐ray absorption and Diffuse Reflectance UV‐Vis spectroscopies showed that during this transformation the Cu II /Cu I reduction, observed under similar conditions at 200 °C, hardly occurred. DFT calculations confirmed the stability of nitrate ligands in the monodentate conformation in [Cu II (NH3 )3 (NO3 )] + complexes when solvated by ammonia. The resulting structure was successfully used to fit the corresponding experimental EXAFS spectra. The gradual change of ligands in the Cu II coordination sphere was confirmed by the blue shifts of both d - d and Ligand to Metal Charge Transfer bands in Diffuse Reflectance UV‐Vis spectra, with formation of features (27500, 32000 and 38000 cm −1 ) ascribable to the mixed‐ligand configuration. Abstract : In the copper mix : The detachment of framework‐interacting Cu‐nitrates in Cu−CHA in a NO/NH3 flow is followed at 50 °C by in situ FTIR, Diffuse Reflectance UV‐Vis and XAS spectroscopies, showing the formation of mixed‐ligand mobile [Cu II (NH3 )3 (NO3 )] + complexes.